Assessing Organizational Legitimacy of Multi Stakeholder Initiatives in the Forest Governance Policy in Indonesia: Insights from the Indonesian National Forestry Council - MUTTAQIN, Tatag; DHARMAWAN, Budi (Journal of Environmental Management and Tourism; Vol 14 No 3 (2023): JEMT, Volume XIV, Issue 3(67), Summer 2023DO - 10.14505/jemt.14.3(67).11, 2023)
National Forestry Council (DKN) is a multi-stakeholder initiative organization (MSI) that was established as a collaborative forum for parties to contribute to Indonesia's forestry governance policy process. As MSI, DKN aims to become a collaborative forum for forestry stakeholders in the policy-making process. The dilemma between institutional status and the ability of constituent representatives is a factor in the decline of their performance and credibility. This research aims to empirically examine the legitimacy of DKN as an MSI using the input and output legitimacy approach. Using semi-structured interviews, snowball sampling, and triangulation approaches, information regarding organizational dynamics was obtained. Based on our empirical findings, we conclude that DKN satisfies all of the criteria for an institution with relatively high input legitimacy and low output legitimacy. DKN involves many stakeholders affected by forestry policies and is able to cooperate successfully in every decision-making process while preserving the rights of each constituent. In particular, DKN does not meet the criteria for output legitimacy in carrying out its role as an MSI by offering policy-adopted recommendations or suggestions.